If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(m + -3) = 15 Reorder the terms: 2(-3 + m) = 15 (-3 * 2 + m * 2) = 15 (-6 + 2m) = 15 Solving -6 + 2m = 15 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2m = 15 + 6 Combine like terms: -6 + 6 = 0 0 + 2m = 15 + 6 2m = 15 + 6 Combine like terms: 15 + 6 = 21 2m = 21 Divide each side by '2'. m = 10.5 Simplifying m = 10.5
| x=18+-0.6y | | y=-sin(7x) | | 20y+12x=360 | | 13p+6q=56 | | 31/4x-2=23 | | 20x+12y=360 | | 3y+8=-17 | | -x^2+20x-91=0 | | 5(x-2)=4(x+2) | | 3(1/4)x-2=2/3 | | (20y+5xy^2)dx+(15x+4x^2y)dy=0 | | 5x-17=-9 | | 4.35x=4.0x+2 | | 4.35x=3.70x+4 | | x+5=20-x | | 4y-1+y+21=5y+20-3y | | 13=22-x | | 5x-3/5 | | (2x+8)(x-2)=144 | | 2.75x+35=2.50x+95 | | a^6-b^6= | | 2.75x+35=3.50x+95 | | 3.55x=2.75x+35 | | 2(x+2)-11=61 | | x^2+200x-5000=0 | | 2.75x+35=3.35x | | y+6=-11 | | 6a+2b-3a+10b= | | 4x^2-12x+9-4y^2= | | 3/8x-1/-4=2 | | 2.45x+95=2.75x+35 | | y=x^3+3x^2 |